2016
DOI: 10.1016/j.neuint.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the excitatory amino acid transporter 3 (EAAT3)

Abstract: The neuronal excitatory amino acid transporter 3 (EAAT3) is fairly ubiquitously expressed in the brain, though it does not necessarily maintain the same function everywhere. It is important in maintaining low local concentrations of glutamate, where its predominant post-synaptic localization can buffer nearby glutamate receptors and modulate excitatory neurotransmission and synaptic plasticity. It is also the main neuronal cysteine uptake system acting as the rate-limiting factor for the synthesis of glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 250 publications
(310 reference statements)
3
55
0
Order By: Relevance
“…Overall, with the exception of tyrosine (TYR), the content of nonessential amino acids was significantly higher in human colostrum than in bovine colostrum (P < 0.05), with asparagine (ASN), aspartic acid (ASP), and cysteine present only in human colostrum. Previous studies reported that glutamic acid (GLU) and ASP were excitatory amino acids, 37 with our results indicating higher content of each, particularly GLU (approximately tenfold higher), in human colostrum relative to that in bovine colostrum. Table 2 shows that glutamine (GLN), serine (SER), and glycine (GLY) content was significantly higher in human colostrum than in bovine colostrum (P < 0.05).…”
Section: Comparison Of 11 Nonessential Amino Acids Between Bovine Andsupporting
confidence: 87%
“…Overall, with the exception of tyrosine (TYR), the content of nonessential amino acids was significantly higher in human colostrum than in bovine colostrum (P < 0.05), with asparagine (ASN), aspartic acid (ASP), and cysteine present only in human colostrum. Previous studies reported that glutamic acid (GLU) and ASP were excitatory amino acids, 37 with our results indicating higher content of each, particularly GLU (approximately tenfold higher), in human colostrum relative to that in bovine colostrum. Table 2 shows that glutamine (GLN), serine (SER), and glycine (GLY) content was significantly higher in human colostrum than in bovine colostrum (P < 0.05).…”
Section: Comparison Of 11 Nonessential Amino Acids Between Bovine Andsupporting
confidence: 87%
“…SLC1A1 mRNA and EAAT3 protein are strongly expressed in the cortex and the striatum and in mesolimbic and nigrostriatal dopaminergic neurons (30)(31)(32)(33). EAAT3 localizes to peri-and postsynaptic regions (32), where it serves three apparent functions: (i) buffering glutamate concentrations around peri/extrasynaptic NMDA and metabotropic glutamate receptors (34); (ii) taking up glutamate as an intracellular precursor for GABA synthesis (35); and (iii) taking up cysteine for glutathione synthesis and protection from oxidative stress (36,37).…”
Section: Significancementioning
confidence: 99%
“…As such, it is theorized that EAAT3/EAAC1 is important for diverse functions not necessarily related to glutamate uptake and recycling. For example, glutamate taken up by EAAT3 in gamma amino-butyric acid (GABA) neurons provides a precursor for further GABA production ( Bjorn-Yoshimoto and Underhill, 2016 ). EAAT3 also displays high affinity for L-cysteine and thus serves as the primary source of intracellular precursor for production of the important antioxidant glutathione (GSH) ( Watts et al, 2014 ).…”
Section: Eaat3mentioning
confidence: 99%
“…Three alternative isoforms are reported for human EAAT3 protein. Two isoforms result from skipping of exon 2 or 11 and have significant implications for predicted protein structure ( Bjorn-Yoshimoto and Underhill, 2016 ). The third isoform, identified in humans and mice, is a result of a secondary internal promoter producing an N-terminal truncated protein ( Porton et al, 2013 ).…”
Section: Eaat3mentioning
confidence: 99%